2009
DOI: 10.1302/0301-620x.91b12.23018
|View full text |Cite
|
Sign up to set email alerts
|

The Avon patellofemoral joint replacement

Abstract: We present a prospective review of the two-year functional outcome of 37 Avon patellofemoral joint replacements carried out in 29 patients with a mean age of 66 years (30 to 82) between October 2002 and March 2007. No patients were lost to follow-up. This is the first independent assessment of this prosthesis using both subjective and objective analysis of outcome. At two years the median Oxford knee score was 39 (interquartile range 32 to 44), the median American Knee Society objective score was 95 (interquar… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

4
22
0

Year Published

2011
2011
2023
2023

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 56 publications
(26 citation statements)
references
References 27 publications
4
22
0
Order By: Relevance
“…These findings substantiate those of an earlier retrospective consecutive case study, where good or excellent functional results were reported, using the Knee Society Score (KSS), in 86% of 'residual' cases at 17 years [6]. Most recently, Odumenya et al [7] and Stark et al [8] have reported excellent functional outcomes with 100% survivorship at 5 and 2 years follow-up, respectively. Therefore, there is some evidence to suggest that PFA provides positive results for patients with isolated patellofemoral arthritis.…”
Section: Introductionsupporting
confidence: 86%
“…These findings substantiate those of an earlier retrospective consecutive case study, where good or excellent functional results were reported, using the Knee Society Score (KSS), in 86% of 'residual' cases at 17 years [6]. Most recently, Odumenya et al [7] and Stark et al [8] have reported excellent functional outcomes with 100% survivorship at 5 and 2 years follow-up, respectively. Therefore, there is some evidence to suggest that PFA provides positive results for patients with isolated patellofemoral arthritis.…”
Section: Introductionsupporting
confidence: 86%
“…Twelve (22%) patients in our series had previous operations on the same knee, which was similar to that reported in other series 92426. Out of these, six knees had previous lateral release performed, while others had chondrectomy earlier for patellar cartilage degeneration.…”
Section: Discussionsupporting
confidence: 87%
“…The Avon prosthesis is the only patellofemoral prosthesis with more than 1000 cases having five-year or longer follow-up, according to the National Joint Registry Report 2010 (UK) 25. However, most of the long-term results have been published by the designers,59 with good short-term results being reported by other centers only recently 2426. We present a large series with a longer followup.…”
Section: Discussionmentioning
confidence: 74%
“…1 ). The search identified 14 eligible studies reporting results from PFA [15-28] and 3 studies reporting results from TKA [29-31] in the treatment of isolated PFOA. There are no published randomised controlled trials comparing PFA to TKA for isolated patellofemoral arthritis, although one has been proposed [36].…”
Section: Resultsmentioning
confidence: 99%
“…There were several studies that were identified in the literature which had good numbers and sound methodology however the primary pre-operative diagnosis was not restricted to PFOA [38,39]. One particular study by Starks [28] and colleagues reported results of the Avon PFA and give an excellent independent verdict of the prosthesis, however, within their population they included one patient who had had a failed autologous chondrocyte implantation of the patella. As the pathology of this condition is limited to the patellofemoral joint and as it was an isolated case, its impact on the overall study was deemed to be small and hence it was included in this review.…”
Section: Studies Reporting Results From Patellofemoral Arthroplastymentioning
confidence: 99%